MANAGING CRITICAL ILL CHILD WITH ACUTE RESPIRATORY FAILURE - Shosholceva M; Kuzmanovska B; Kartalov A; Ristovski S; Srceva M; Karadjova D; Tolevska M (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University, Skopje, 2017)
Children with acute respiratory failure (ARF) present the commonest group of critical ill patients for admission in pediatric intensive care unit (PICU). Respiratory developmental differences between children and adults render this susceptible group to altered response to disease process, various clinical manifestations and interventions for respiratory failure. Appropriate decisions for a proactive and life-saving management of the critically ill child with ARF can be provided recognizing three distinctive clinical profiles: mechanical dysfunction of airways, neuromuscular and breathing dysfunction. Beside this, assessment of many physiologic variables of the respiratory system in children with ARF helps in identification of the development of the respiratory failure and serves as a guide therapy for good outcome. Therapeutic modalities and strategies for respiratory failure in children vary depending on the underlying cause. Interventions include supportive and specific therapy. Maintenance of body temperature is of major importance while fluid therapy, monitoring and assessment are additional necessary measures that are undertaken at first. Supportive therapy include securing the airways, oxygen by mask, nasal cannula or head box, proper positioning, nebulization if indicated, and physiotherapy. Specific measures include oxygen therapy and mechanical ventilatory support. Prognosis and outcome depend on the presence of the disease on admission using a number of scoring system, appropriate follow up and adequate therapeutic treatment.
Keywords: acute respiratory failure; critical ill child